National analysis of dental teleconsulting of the Brazilian Telehealth Program - Lígia Cristelli PAIXÃO; Efigênia Ferreira FERREIRA; Antônio Paulino RIBEIRO-SOBRINHO; Renata Castro MARTINS (Sociedade Brasileira de Pesquisa Odontológica, 2022)
Abstract This cross-sectional study nationally evaluated asynchronous dental teleconsulting services offered by the Telehealth Brazil Networks Program, using the 2019 Telehealth Results Monitoring and Evaluation System database and considering Brazilian regional differences. The following teleconsulting variables were collected: dentist's sex and specialty, date/time of question and answer, response time; dental specialty, professional satisfaction, and patient referral. Five Brazilian regions were socioeconomically characterized according to the Human Development Index, estimated population, Gini coefficient, coverage of dental specialty centers, oral health teams in Family Health Strategy, and oral health teams in primary health care (PHC). In total, 2,703 teleconsulting sessions occurred in Brazil in the analyzed period. The Southeast exhibited the highest demand (49.1%). Most dentists were female (60.6%) and were dental surgeons from the Family Health Strategy (61.3%). Most teleconsulting sessions occurred during working hours (85.5%) and questions were answered within 72 hours (66.7%). Level of satisfaction and avoidance of referral yielded rates of 90.9% and 66.8%, respectively, among dentists who answered about these topics. Semiology was the most frequently demanded area in teleconsulting (33.9%). The different demands from the regions reflected regional differences. The most frequently demanded specialties represent the Brazilian PHC scenario. Professionals incorporated teleconsulting into their work routine and most teleconsultants responded within the stipulated timeframe. Professional feedback should be encouraged.